Impact of Organizational Culture and Job Training on Employee Performance in the Indonesian Shipbuilding Industry - Pasaribu, Reynaldi Krisvinus; Rini, Hesty Prima (Universitas Pakuan, 2025)
This study aims to examine the role of organizational culture and training in enhancing employee performance at PT. PAL Indonesia, a state-owned enterprise in the shipbuilding industry. The company has faced performance challenges related to generational gaps and skill disparities amid the rapid transformation toward Industry 4.0. Using a quantitative approach, data were collected through questionnaires distributed to 56 employees in the warship production division, selected using a saturated sampling technique. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SMARTPLS software. The results reveal that both organizational culture and training have a positive and significant effect on employee performance. A strong organizational culture, particularly one emphasizing attention to detail, collaboration, and adaptability, enhances employee commitment and work effectiveness. Moreover, relevant and goal-oriented training programs contribute to improved skills, motivation, and productivity. The study concludes that integrating a cohesive organizational culture with continuous and adaptive training programs can effectively bridge generational and competency gaps, fostering higher performance and organizational competitiveness in the global maritime industry. These findings highlight the strategic importance of human resource development in sustaining innovation and productivity in state-owned industrial enterprises.